Estudo dos aspectos da produção da kombucha na indústria - Santos, Brena Larissa Medeiros (2021)
The increased search for a healthier lifestyle has led people to look for foods that fit this style and amidst the explosion of access to social networks, being healthy and consuming certain products has become a trend. As a functional food, kombucha has been part of the routine of thousands of people who seek to combine food with health, popular around the world and constantly growing in Brazil, the kombucha market is the fastest growing in the functional drinks sector with a estimated movement of up to 1.8 billion dollars by the end of the decade. Its popularity is not for nothing, in addition to being a functional food, kombucha is made with simple raw materials and has a simplified production process, which is why the number of kombucha producing industries is only growing. Through a collection of literature and virtual visits to two kombucha industries in Brazil, this work aimed to present the industrial production process of kombucha, evaluate the useful life of some kombucha commercialized, in addition to creating a layout of the production area of a kombucha industry. It was observed that even with variations, the industrial production processes were similar to the literature, and it can be concluded that the studied industries are still growing, evolving to a process with more added technology. The shelf life among the beverages of the studied industries was the same, but it varied a lot when compared to the kombuchas evaluated in the market. The layout created will be essential so that the industries created can adapt to current legislation